PENGARUH PROGRAM PELATIHAN SERVICE EXCELLENCE DAN PELATIHAN POSITIF KOMUNIKASI TERHADAP KUALITAS PELAYANAN FRONTLINE PADA SUSHI YAY! CABANG JAKARTA DAN BEKASI - Euis Yunita Putri; Imelda Sari (Politeknik Negeri Lhokseumawe, 2026)
Sushi Yay! is a brand of PT. Yay Enak Semua, a fast-food restaurant that offers a variety of sushi, nigiri, sashimi, and local sushi innovations. This research seeks to examine the effect of service excellence training and positive communication on the service quality of Sushi Yay! frontline in the Jakarta and Bekasi areas. The research sample consisted of 59 staff. Sample selection was conducted using a non-probability method with a purposive sampling approach. This study adopted a quantitative method, and the questionnaire results were processed through SPSS 21. The findings indicated that, individually, service excellence training and positive communication training influenced the service quality of frontline staff. simultaneous analysis also shows that both service excellence training and positive communication training contribute significantly to improving service quality at Sushi Yay! branches in Jakarta and Bekasi. Thus, service excellence and positive communication training are proven to be valid and reliable in improving frontline service quality. Keywords: Service Excellence, Positive Communication, Service Quality.